Tweetalige Aanleerderswoordeboek. Bilingual Learner’s Dictionary - Otto, Anna Nel (Lexikos, 1994)
In this review article the discussion concentrates on the purpose of learner’s dictionaries, viz. to improve the communicative competence of a foreign language learner, and on usage guidance in learner’s dictionaries. It is pointed out that target users should be clearly identified and their needs assessed before the dictionary is compiled. The function of the dictionary should also be determined and throughout be taken into account, and the dictionary should ideally be an appropriate medium for both decoding and encoding. It seems as if the TA is a very appropriate medium for decoding, because the vocabulary has been restricted to a fairly simple level, the grammatical information is uncomplicated and the example sentences consist mainly of words included as headwords. The TA is, however, not altogether an appropriate medium for encoding. Correct pronunciation is not guaranteed, because only syllabification and the main stress are indicated in words. Grammatical guidance is also not given to such an extent that learners will be able to generate correct sentences on their own. The role that contrastive analysis and error analysis can play to anticipate learners’ problems is also pointed out. Example sentences mostly reflect everyday situations, but not all example sentences sound natural or reflect typical language usage. Very little CA- and EN-collocations are recorded in the TA and the collocations which are recorded, are not treated consistently. Keywords: bilingual learner’s dictionary, ca-collocations, collocations, communicative competence, contrastive analysis, decoding, encoding, en-collocations, error analysis, example sentences, grammatical guidance, labels, pronunciation guidance, purpose of dictionary, target users, usage guidance, usage notes